2020
DOI: 10.3390/nu12082391
|View full text |Cite
|
Sign up to set email alerts
|

A Five-Ingredient Nutritional Supplement and Home-Based Resistance Exercise Improve Lean Mass and Strength in Free-Living Elderly

Abstract: Old age is associated with lower physical activity levels, suboptimal protein intake, and desensitization to anabolic stimuli, predisposing for age-related muscle loss (sarcopenia). Although resistance exercise (RE) and protein supplementation partially protect against sarcopenia under controlled conditions, the efficacy of home-based, unsupervised RE (HBRE) and multi-ingredient supplementation (MIS) is largely unknown. In this randomized, placebo-controlled and double-blind trial, we examined the effects of H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
110
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(135 citation statements)
references
References 125 publications
1
110
0
1
Order By: Relevance
“…Therefore, it is possible to assume that many individuals under social isolation do not consider the home as an environment conducive to physical activity [14]. As closures of parks, trails, gyms and beaches make it more difficult for individuals to be active, it is important that health professionals should provide information to population about different possibilities of home exercise programs [40][41][42]. Lack of motivation was the second most prevalent barrier in the current study, although in relative terms it was less than other studies conducted before the pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is possible to assume that many individuals under social isolation do not consider the home as an environment conducive to physical activity [14]. As closures of parks, trails, gyms and beaches make it more difficult for individuals to be active, it is important that health professionals should provide information to population about different possibilities of home exercise programs [40][41][42]. Lack of motivation was the second most prevalent barrier in the current study, although in relative terms it was less than other studies conducted before the pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…These exercises may enhance the myofibrillar protein synthesis, and it has been suggested that it was due to nutrient-stimulated vasodilatation and improvement in nutrient delivery to muscle [ 68 ]. Additionally, the results indicated that the effects of these types of physical activity, particularly resistance training, may be impacted by nutritional status [ 69 ] and nutrient supplementation [ 70 ]. Ethnicity is also known to influence muscle parameters and nutritional status [ 71 , 72 ], but we did not adjust our analyses on this variable since the included participants in our cohort were homogeneous in terms of ethnicity.…”
Section: Discussionmentioning
confidence: 99%
“…As performance-related studies assessed health and safety markers, evidence began to accumulate that creatine supplementation may also offer some health and/or therapeutic benefits as we age [ 4 , 12 , 14 , 67 , 69 , 70 , 71 , 131 ]. In this regard, creatine supplementation has been reported to help lower cholesterol, triglycerides and/or manage blood lipid levels [ 77 , 132 , 133 ]; reduce the accumulation of fat on the liver [ 133 , 134 ]; decrease homocysteine thereby reducing risk of heart disease [ 30 , 135 ]; serve as an antioxidant [ 30 , 136 , 137 , 138 , 139 ]; enhance glycemic control [ 1 , 11 , 140 , 141 , 142 , 143 ]; reduce the progress of some forms of cancer [ 8 , 17 , 18 , 135 , 144 , 145 , 146 , 147 ]; increase strength and muscle mass [ 2 , 9 , 13 , 67 , 70 , 71 , 93 , 99 , 101 , 148 , 149 , 150 , 151 , 152 ,…”
Section: General Health Benefitsmentioning
confidence: 99%